2005
DOI: 10.1093/rheumatology/kei107
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of primary Sjögren's syndrome in north-west Greece, 1982–2003

Abstract: The estimated incidence and prevalence of pSS in this study were slightly higher in comparison with data from other studies based on physician-diagnosed cases. The prevalence was significantly lower when compared with the findings of studies based on the examination of a sample of the general population. Mortality rates did not differ significantly between pSS patients and the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
87
7
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(111 citation statements)
references
References 23 publications
10
87
7
7
Order By: Relevance
“…In this setting, it is conceivable that patients with primary SS may also have an increased CV risk. However, the incidence of CV diseases (CVDs) and their impact on survival in primary SS remain unclear, although some studies on large cohorts have found that CVDs are one of the leading causes of mortality in these patients (7,8). Similarly, the presence of subclinical atherosclerosis in primary SS has been scarcely investigated in comparison with RA and SLE (9 -15).…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, it is conceivable that patients with primary SS may also have an increased CV risk. However, the incidence of CV diseases (CVDs) and their impact on survival in primary SS remain unclear, although some studies on large cohorts have found that CVDs are one of the leading causes of mortality in these patients (7,8). Similarly, the presence of subclinical atherosclerosis in primary SS has been scarcely investigated in comparison with RA and SLE (9 -15).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A study of 467 patients by Garceau and Chalmers from 1963 demonstrated that only 30-40% of them survived 12 months after the diagnosis of oesophageal varices. 1 The most common mode of death was gastrointestinal haemorrhage (34%). Similarly, in 1981, Graham and Smith found a 6-week mortality in 42% of patients with variceal bleeding confirmed by endoscopy, …”
Section: Introductionmentioning
confidence: 99%
“…18 According to the classification criteria of the American-European Consensus Group, 19 the prevalence of pSS is far lower than previously assumed, and the reported male/female ratio of 1:9 seems to lie more in the range of 1:20. 20 Use of the American-European Consensus Group criteria will probably result in the participation of fewer males, as well as younger patients in general, and more severely ill patients in future cohort investigations. 21 Information regarding age at disease onset has changed over the last decade, as recent studies are indicating an onset age of approximately 45 years, compared to 56 in earlier studies.…”
Section: Methodsmentioning
confidence: 99%